Breaking the vicious cycles of self-criticism: a qualitative study on the best practices of overcoming one’s inner critic - Bronislava Šoková; Katarína Greškovičová; Júlia Halamová; Martina Baránková (BMC Psychology)
Abstract Despite continuous efforts to understand self-critical inner dialogues, little is known about the best practices people use to overcome their self-critics. In this study, we aimed to analyse the self-critical cycles of participants who scored high on coping to understand the most adaptive strategies and responses to the self-critic. The consensual qualitative analysis was performed by a team of three researchers and one auditor. The high scorers were identified from a convenience sample of 1,683 participants. Twenty participants, 14 women and 6 men, were randomly chosen from the sample of individuals who scored high in self-reporting inventory of coping. In-depth repeat interviews were conducted with 15 participants for the main analysis, and 5 were added to check the data saturation. The results revealed three core themes – I am okay but I need improving; I am okay but improving would help; and I am not okay and it is hard to be different. Furthermore, six main types of self-critic emerged from the data: Teamster, Non-feeler, Worrier, Not good enough for self, Not good enough for others, and Hated self. Self-critic sequences included the trigger or specific situation evoking that self-critic; accompanying emotions and/ or self-awareness; a particular kind of self-criticism and self-compassionate and/or self-protective responses to the self-critic that form part of coping. The results supported the Emotion Focused Theory of change, with self-compassionate and self-protective responses being aimed at various types of self-critic. Self-critic specific nuances were also identified. The study provided the possibilities of working with different types of inner critics and could alleviate the suffering caused by them.